The Expression of PD-L1 and B7-H4 in Thymic Epithelial Tumor and Its Relationship With Tumor Immune-Infiltrating Cells - Yan, Xiaotian; Feng, Jie; Hong, Bo; Qian, Yun (Frontiers in Oncology, 2021)
Background: PD-L1 and B7-H4 have been reported to be expressed in various malignancies and are considered as promising prognostic factors and potential immunotherapy targets. Methods: We analyzed the correlation between the expression of PD-L1 and B7-H4 transcriptomes and clinicopathological characteristics in 121 TET patients from The Cancer Genome Atlas (TCGA) database. The immune-infiltration levels in the TET microenvironment were estimated using ssGSEA and quanTiseq algorithms. We collected 80 TET cases from 2008 to 2015. PD-L1、B7-H4、FOXP3 and CD163 protein expression in tumor tissues were detected by immunohistochemistry. Results: TCGA database showed PD-L1 mRNA levels can predict the OS (P = 0.018) and DFS (P = 0.033) of TET patients. B7-H4 mRNA levels were positively related to the World Health Organization (WHO) pathological classification (P = 0.003) but not correlated with patient prognosis. Immune infiltration analysis showed PD-L1 is positively correlated with Tregs and M2 macrophages, B7-H4 is positively correlated with Tregs. Patients with high PD-L1 and Tregs or M2 macrophages, high B7-H4 and Tregs had a worse prognosis. Immunohistochemistry showed PD-L1 expression was positively correlated with the WHO pathological classification and Masaoka stage (P = 0.025, 0.003) and high PD-L1 expression can predict the poor OS of patients (P = 0.043); B7-H4 was also positively correlated with WHO pathological classification and Masaoka stage (P = 0.036, 0.049). However, B7-H4 expression did not correlate with patient prognosis. Evaluation of co-expression patterns showed TET patients with a high-grade WHO pathological classification harbored a 44.4% co-expression of PD-L1 and B7-H4. In addition, we found the expression level of PD-L1 is positively correlated with FOXP3 and CD163 (P = 0.004, P = 0.029) and B7-H4 is positively correlated with FOXP3 (P = 0.037). High PD-L1 combined with High FOXP3 and High CD163, High B7-H4 combined with High FOXP3 can be used to predict the poor prognosis of TET patients (P = 0.026, 0.031, 0.028, respectively). Conclusion: PD-L1 and B7-H4 were related to the aggressiveness of TET and their expression level can indicate the suppressive immune microenvironment. Combined with FOXP3 and CD163, PD-L1 and B7-H4 can indicate a poor prognosis of TET.